2021
DOI: 10.14423/smj.0000000000001245
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in a Mississippi Community Hospital

Abstract: This document contains the image that you requested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In this systematic review and meta‐analysis, the majority of studies reported that patients with overweight and obesity had shown an increased rate of hospitalization and ICU admissions due to respiratory failure and the development of acute respiratory distress syndrome (ARDS) with cytokine storm 28,39,71,162,166 . Patients with overweight and obesity admitted to ICU required oxygen therapy either by invasive or non‐invasive mechanical ventilation (IMV or NIMV) more than patients with normal weight 73,88,118,135,151,155,177,184–194 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review and meta‐analysis, the majority of studies reported that patients with overweight and obesity had shown an increased rate of hospitalization and ICU admissions due to respiratory failure and the development of acute respiratory distress syndrome (ARDS) with cytokine storm 28,39,71,162,166 . Patients with overweight and obesity admitted to ICU required oxygen therapy either by invasive or non‐invasive mechanical ventilation (IMV or NIMV) more than patients with normal weight 73,88,118,135,151,155,177,184–194 .…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the studies included in the two groups is provided in Data S1 12–194 . The literature search yielded a total of 826 citations.…”
Section: Data Extractionmentioning
confidence: 99%
“…Some previous publications have conducted studies on the effects of COVID-19, focusing on specific secondary hospitals or limited time periods. These studies provided information about the demographic characteristics and outcomes of the patients included in their respective cohorts [ 70 , 71 , 72 , 73 ]. Although we recognize that there may be regional variations in the characteristics of COVID-19, and we acknowledge that our findings may not directly apply to other settings, it is important to note that our study encompassed a period of 27 months during the pandemic and involved over 3000 hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients with coronavirus disease 2019 (COVID-19) requiring mechanical ventilation have a mortality rate of approximately 56% 1 . We recently published our experience with hospitalized COVID-19 patients at the community hospital level, which showed that our outcomes were similar to those at larger centers 2 . This retrospective study was designed to evaluate overall differences between survivors and nonsurvivors requiring mechanical ventilation for COVID-19 respiratory failure in two community hospital intensive care units (ICUs).…”
mentioning
confidence: 99%
“… 1 We recently published our experience with hospitalized COVID-19 patients at the community hospital level, which showed that our outcomes were similar to those at larger centers. 2 This retrospective study was designed to evaluate overall differences between survivors and nonsurvivors requiring mechanical ventilation for COVID-19 respiratory failure in two community hospital intensive care units (ICUs). Differences in timing of intubation and ventilator parameters were specifically evaluated.…”
mentioning
confidence: 99%